Association between depression and risk of atrial fibrillation and stroke in patients with psoriasis: a Danish nationwide cohort study. (11th June 2015) - Egeberg, A.; Khalid, U.; Gislason, G.H.; Mallbris, L.; Skov, L.; Hansen, P.R.
Summary: Background: Psoriasis and depression are associated with atrial fibrillation (AF) and stroke, but the influence of depression on the risk of stroke and AF in patients with psoriasis has not been examined. Objectives: We investigated the impact of depression on the risk of stroke and AF in patients with psoriasis in a nationwide cohort. Methods: Data on all Danish citizens aged ≥ 18 years between 1 January 1997 and 31 December 2011 ( n  =   5 251 888) were linked at the individual level in nationwide registers. Incidence rates (IRs) per 1000 person‐years were calculated, and hazard ratios (HRs) adjusted for age, sex, concomitant medication and comorbidity were estimated by multivariate Cox regression models. Results: There were 56 496 and 11 357 incident cases of mild and severe psoriasis, respectively. Incident depression occurred among 12 788 cases with mild and 3261 cases with severe psoriasis. IRs per 1000 patient‐years of AF were 3·21, 5·02, 8·41, 5·39 and 7·41; and IRs of stroke were 2·62, 3·09, 6·71, 3·62 and 9·03 for the reference population, mild psoriasis without depression, mild psoriasis with depression, severe psoriasis without depression and severe psoriasis with depression, respectively. The respective HRs for new‐onset AF were 1·14 [95% confidence interval (CI) 1·08–1·33], 1·19 (95% CI 1·06–1·33), 1·32 (95% CI 1·15–1·53) and 1·74 (95% CI 1.43–2·11), respectively. For stroke the HRs were 1·63 (95% CI 1·43–1·85) in patients with mild psoriasis and depression and 2·47 (95% CI 2·07–2·95) in patients with severe psoriasis and depression. Conclusions: In patients with psoriasis, depression is associated with an increased risk of incident AF and stroke. Abstract : What's already known about this topic? Patients with psoriasis have increased risk of atrial fibrillation and stroke. What does this study add? Depression was associated with increased risk of stroke, and an incremental increase in risk of atrial fibrillation in patients with psoriasis. No increased risk of stroke was observed in patients with psoriasis without depression.